Factors influencing consumer adoption of electric vehicles: A literature review - Rizky Novera Harnaningrum; Meidina Kalse Boer; Dessy Damayanthy (Privietlab, 2026)
Electric vehicles (EVs) are considered a key method for reducing transportation emissions, improving city air quality, and supporting sustainable travel. Although global EV sales have grown rapidly, the adoption rates differ by region. Many countries still face significant challenges in getting more people to use electric EVs. This study examines research on what affects people’s decisions to buy EVs. It uses a method to group the findings into six main areas: economic and financial, technological, behavioral and psychological, infrastructure and policy, socio-demographic, and market and industry factors. The study shows that economic factors, such as the price and total cost of owning an EV, are important for buyers. Technological factors such as battery range, charging time, and reliability also affect consumer trust. However, other factors such as how useful and easy to use people think EVs are, their environmental values, social influence, and what they know about EVs also matter. Policies and charging infrastructure are crucial, especially when they provide long-term support and reduce uncertainty. Industry factors, such as brand trust and aftersales service, help reduce perceived risks. Overall, the study suggests that to increase EV use, strategies need to be coordinated and specific to each area of focus. They should address costs, technology, trust, awareness, and everyday use, especially where EV adoption is low.